Escherichia coli and Salmonella sp. on some lettuce in the traditional market of Banyuwangi Regency - Eka Yunita Wulandari; Sinta Nuriyah Putri Ayu; Nur Lailatul Hanifa; Brunika Mega Handayani; Adhinda Fisabilla (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2024)
Escherichia coli is the main pathogenic bacteria which causes diarrhea in humans and the fourth highest cause of death which occurs all age groups. Salmonella sp is the cause of typhoid fever and findings of 350-810 cases each year. Diarrhea and typhoid fever are closely related to the consumption of raw vegetables, such as lettuce. This study aimed to analyze the contamination of E. coli and Salmonella sp on some lettuces in Traditional Markets of Banyuwangi Regency. This research was an analytic descriptive study using a cross-sectional design at the Laboratory of Microbiology, STIKES Banyuwangi from 6 to 11 June 2022 using 6 lettuces as research samples which were selected by accidental sampling. All (100%) lettuce samples in this study were contaminated with >1,100 CFU/ml E. coli. All (100%) samples in this study were positively contaminated by Salmonella sp with various contamination number, such as: 0.82x104; 0.47x104, 1.90x105, 2.05x106, 1.00x105 and 1.25x106 CFU/ml, respectively. All six lettuces obtained from the Traditional Market of Banyuwangi Regency did not meet the microbiological quality specified by SNI, indicating that they were not suitable forÂ  direct (raw) consumption.